Local Diagnosis: Analysis and Evaluation of Young People's Occupational Situation in Cipolletti City - Gluschnaider, Daiana (2016)
Following paper intends to establish, by articulating theory with basis on stadistical local, national and regional data, a diagnosis that allows to base future actionsintended to improve young people's occupational situation in Cipolletti city. Our focus in these developments propose a device to approach young people's social integration, conceived as specific actions for mental health promotion and prevention. Problematic and economic impact will be characterized, considering the influence that work has on youth subjectivity's core and identity construction, as it enables psico-social integration and allows to counteract the negative effect that unemployment has on adulthood constitution.